2018
DOI: 10.1159/000489258
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Tolvaptan for Refractory Ascites in Patients with Advanced Cirrhosis

Abstract: Aims: The study aimed to evaluate the effects of tolvaptan treatment on survival of patients with decompensated liver cirrhosis with refractory ascites. Methods: This multicenter, retrospective, observational study included patients with cirrhosis who were treated with tolvaptan for hepatic ascites refractory to conventional diuretics. Patients who could and could not decrease accompanying diuretics within 1 month after tolvaptan administration were defined as the “Decreased” and “Not-decreased” groups, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…39,40 Moreover, one study assessed the efficacy of tolvaptan in elevating serum sodium in cirrhotic patients with hyponatremia, 41 while another one included exclusively tolvaptan non-responders. Four studies were excluded after reading the full text.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Moreover, one study assessed the efficacy of tolvaptan in elevating serum sodium in cirrhotic patients with hyponatremia, 41 while another one included exclusively tolvaptan non-responders. Four studies were excluded after reading the full text.…”
Section: Resultsmentioning
confidence: 99%
“…Two of them evaluated predictive factors of tolvaptan response only with univariate logistic regression, and thus, they provided inadequate data to be included in the quantitative metaanalysis. 39,40 Moreover, one study assessed the efficacy of tolvaptan in elevating serum sodium in cirrhotic patients with hyponatremia, 41 while another one included exclusively tolvaptan non-responders. 42 Quality assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [19][20][21][22][23][24][25][26][27] were included in the analysis, with a total of 736 patients. Among them, 451 patients presented clinical response to tolvaptan therapy, while the rest 285 were judged as nonresponders.…”
Section: Included Studiesmentioning
confidence: 99%
“…Multivariate analyses demonstrated that not only HCC complication (p=0.02) but also early reexacerbation (p<0.01) was identified as independent predictors for OS in responders (Table 5). It has been reported that a decrease in conventional diuretic dosages was independent prognostic factor of survival in patients treated with tolvaptan for refractory ascites [13]. We then examined OS in patients with dose-reduction of conventional diuretics (n=16) or without (n=39).…”
Section: Prognosis In View Of Tolvaptan Responsementioning
confidence: 99%